2013
DOI: 10.1007/s10995-013-1420-9
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Health Insurance Coverage on Access to Healthcare in Children Entering Kindergarten

Abstract: To examine access to healthcare and health outcomes for kindergartners as they relate to insurance status and type. For the 2008, 2009, and 2010 school years, surveys were distributed to parents with a child entering kindergarten in the state of Nevada. Surveys asked parents to provide information about their child concerning their insurance status, routine medical care, medical conditions, and health behaviors. Compared to their insured peers, uninsured kindergartners were less likely to have had a check-up i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…An urban-rural gap in access to dental care is well-documented in the literature (Guay, 2004; Skillman et al , 2010), which may explain these results. Further, and in line with previous research, dental care serves is an indicator for access to in healthcare (Haboush-Deloye et al , 2014; Elwell-Sutton et al , 2017). As such, it is reasonable to consider that this relationship is indicative of engagement in preventive services more generally.…”
Section: Discussionsupporting
confidence: 82%
“…An urban-rural gap in access to dental care is well-documented in the literature (Guay, 2004; Skillman et al , 2010), which may explain these results. Further, and in line with previous research, dental care serves is an indicator for access to in healthcare (Haboush-Deloye et al , 2014; Elwell-Sutton et al , 2017). As such, it is reasonable to consider that this relationship is indicative of engagement in preventive services more generally.…”
Section: Discussionsupporting
confidence: 82%
“…Our urban ED patient population is predominantly publicly insured which may be associated with less access to primary care. [36, 37] Therefore, rates of PCP and specialist follow-up from our study may not be generalizable. Furthermore, parents may have felt the ED visit adequately addressed their concerns and concluded further medical care was unnecessary.…”
Section: Limitationsmentioning
confidence: 93%
“…Based on this research, findings indicate that the majority of the adolescents in this study have both public and private insurance. According to Haboush-Deloye et al (2014), the Affordable Care Act (ACA) will make healthcare available to more children. The catalyst for this new legislation centers around providing more people access to healthcare, reducing the cost of healthcare, and extending the accessibility of healthcare insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies have shown an impact on the utilization of health insurance among adolescents. Haboush-Deloye et al (2014) concluded that children ages 0-5 that did not have insurance and those with public insurance had a different knowledge of their accessibility to healthcare coverage and utilization than those with private insurance. Researchers have also recognized different states where Medicaid programs treat adults with obesity; although, a few states utilize the EPSDT program which covers children with obesity (Lee et al, 2010).…”
Section: Introductionmentioning
confidence: 99%